Nonmuscle myosin light chain kinase activity modulates radiation-induced lung injury - Wang, Ting (Pulm Circ, 2016)
Abstract. Radiotherapy as a primary treatment for thoracic malignancies induces deleterious effects, such as acute or subacute radiation-induced lung injury (RILI). Although the molecular etiology of RILI is controversial and likely multifactorial, a potentially important cellular target is the lung endothelial cytoskeleton that regulates paracellular gap formation and the influx of macromolecules and fluid to the alveolar space. Here we investigate the central role of a key endothelial cytoskeletal regulatory protein, the nonmuscle isoform of myosin light chain kinase (nmMLCK), in an established murine RILI model. Our results indicate that thoracic irradiation significantly augmented nmMLCK protein expression and enzymatic activity in murine lungs. Furthermore, genetically engineered mice harboring a deletion of the nmMLCK gene (nmMLCK(−/−) mice) exhibited protection from RILI, as assessed by attenuated vascular leakage and leukocyte infiltration. In addition, irradiated wild-type mice treated with two distinct MLCK enzymatic inhibitors, ML-7 and PIK (peptide inhibitor of kinase), also demonstrated attenuated RILI. Taken together, these data suggests a key role for nmMLCK in vascular barrier regulation in RILI and warrants further examination of RILI strategies that target nmMLCK.